TVET teacher education on the threshold of internationalisation - Bünning, Frank [Herausgeber]; Zhao, Zhiqun [Herausgeber] (UNEVOC, 2006)
This book has been written as a result of the conference "Developemt and Implementation of a Master Degree Standard for Teacher and Trainer Education in TVET in East and South East Asia", which took place at the University of Tianjin, China, in December 2005. The conference represents an outcome of the close cooperation between InWEnt - Capacity Building International of Germany, the Ministry of Education (MoE), Beijing, China and UNESCO-UNEVOC, and set a precedent for the further development of Master degree programmes in TVET. At the conference, various existing Master degree programmes were discussed in the context of an international framework developed at an earlier conference in Hangzhou, China. The structure and content of Master degree programmes of Asian universities were introduced and discussed with particular regard to the implementation of the international framework together with broader aspects of provision impacting on TVET. (BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; P 3.2.3 Lehrer; I 2.1 Deutschland; I 2.3.4 Asien; Berufsschullehrer; Lehrerbildung; Reform; Internationale Zusammenarbeit; Internationaler Vergleich; Bundesrepublik Deutschland; China